Biodegradation of Diesel Contaminated Soil Using Single Bacterial Strains and a Mixed Bacterial Consortium - Jabbar, Noor Mohsen; Kadhim, Estabriq Hasan; Mohammed, Alaa Kareem (Al-Khwarizmi Engineering Journal, 2018)
This study was conducted to assess the hydrocarbon degradation abilities of Sphingomonas paucimobilis, Pentoae species, Staphylococcus aureus, and Enterobacter cloacae, which isolated from diesel contaminated soil samples. Single strains and mixed bacterial consortia have been investigated their ability to degrade 1.0 % (v/v) of diesel oil in Bushnell- Haas medium as sole.carbon.and.energy.source. At temperature 30∘C, the individual.bacterial.isolates exhibited low growth and low degradation.than did the.mixed. bacterial.culture. After 28 days.of incubation the.combination.of four isolates degraded.an upper limit.of diesel 88.4%. This was. continued.by 85.1% by S. paucimobilis, 84 % by Pentoae sp., 79% by S.aureus, and 74% by E. cloacae. For further evidence of the biodegradation effect of these isolates individually and as a mixed culture, which was supported by the use of technology chromatography confirming the occurrence of biodegradation. The results showed that the isolated bacteria are effective in biodegradation of diesel spills when used separately. It also confirmed the better biodegradability when used together in a mixed -culture.